Analisis Yuridis Putusan Hakim Dalam Tindak Pidana Perdagangan Orang Studi Kasus Putusan Nomor 1656/Pid.Sus/2023/PN Mdn - Iqbal Nuriswandi (CV. ITTC INDONESIA, 2024)
Human trafficking is a serious crime involving the exploitation of human beings through deception, coercion, or violence for purposes such as forced labor, slavery, or sexual exploitation. Human trafficking often involves organized criminal networks that operate across national borders, targeting vulnerable individuals such as women, children, and migrants. In the legal context, various international and national laws have been implemented to combat and prevent human trafficking, such as the Palermo Protocol and Law Number 21 of 2007 in Indonesia. Law enforcement efforts include investigation, prosecution, and providing protection to victims. Eradication of human trafficking requires cooperation between the government, non-governmental organizations, and the wider community to create awareness, reduce risk factors, and support victim rehabilitation.The criminal activity that is considered rampant in Indonesia, human trafficking, threatens people's lives. The problems discussed are how the laws and regulations regarding human trafficking in Indonesia, especially the Law on Human Trafficking and the Criminal Code, are regulated and how perpetrators of human trafficking are given criminal sanctions. This study aims to analyze the basis for judges' considerations regarding the crime of human trafficking and the application of sanctions in the legal system. A normative legal approach is used in this study. This approach looks at the problem of legal literature studies, such as books or articles on human trafficking, as primary legal materials and secondary legal materials. The results of this study indicate that human trafficking is increasing in various countries, including Indonesia, and in developing countries, thus attracting the attention of the world, especially the UN. Human trafficking is included in the category of criminal acts or more precisely special criminal acts. Indonesian criminal law regulates it with various provisions. The provisions include prohibitions and eradication as stated in the Criminal Code, Legislation and Draft Criminal Code Articles 546-561 concerning human trafficking. The application of these sanctions is threatened by criminal law with imprisonment and fines. People involved in human trafficking have personal or group interests to seek profit with an organized and systematic mode of operation.